Moving towards embracing sustainability: learning from doing in the extended mega urban region, Kuala Lumpur - Azliyana Azhari,; Nor Fairuz Abu Bakar,; Siti Umira Sulaiman,; Najihah Mat Lazim,; J. J. Lajuni,; Abdul Samad Hadi,; Ahmad Fariz Mohamed,; Shaharudin Idrus,; Abdul Hadi Harman Shah, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
The embracing of sustainability and liveability of an extended urban region depends on several underlying factors related to the three pillars of sustainable development. We have identified some of these factors: the soundness of collaboration between stake holders to create functioning institutions; effective governance to ensure feasible implementation and monitoring of plans and policies, the consideration related to the physical environment, creation of favourable social sphere, and balanced economic drivers such as industrial and retail diversity. In ensuring Malaysia’s rapid development, the industrial sector was promoted, thus encouraging domestic and foreign investments and diversified industrial activities. Industrial growth is important to boost up the economic growth. However, the growth of industrial areas in cities makes it a very vulnerable environment for people to live in, for their pollution threats. Retailing is the main component that contributes to the liveability of a city centre because this will encourage residents to visit the central business district. However, for traffic congestions there is a need for regional redistribution of marketing such as regional shopping complex. Retail planning is compulsory in order to sustain from either the arrangement or distribution of the shops. Seremban Town Centre showed that the retail outlet has moved to sell “high end” products. Education is one of an essential tool for achieving sustainability. An education for sustainable development is based on an integrated approach to economic, environmental and societal development as well as encompasses a broad range of related issues. Governance in sustainable development institutions can refer to the procedures and processes as a bridge that will link to sustainable development. The process of effective governance in achieving sustainable development requires the proactive involvement of all parties.